Tianshan Orogen along the Silk Road (Volume 3): Orogen links, geochemistry, geochronology, mineral deposits, and environments. (25th July 2018) - Li, Sanzhong; Suo, Yanhui; Li, Rongxi; Yu, Shengyao; Yang, Gaoxue; Somerville, I.
Abstract : This special issue (Volume 3) belongs to the special issues on the orogens along the Silk Road. We selected 34 papers to focus on the mineral deposits, orogeny‐links, geochemistry, geochronology, and environments related to the Tianshan Orogen of the Silk Road. We hope that these papers will highlight more geological research along the Silk Road to promote the construction and development of the Road and Belt.